2022
DOI: 10.3390/plants11202773
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Phytochemical and Bioactive Potential of Three Hypericum Species from Romanian Spontaneous Flora: H. alpigenum, H. perforatum and H. rochelii

Abstract: Hypericum perforatum L., also known as St. John’s Wort, is recognized worldwide as a valuable medicinal herb; however, other Hypericum species were intensively studied for their bioactive potential. To fill the research gap that exists in the scientific literature, a comparative evaluation between H. alpigenum Kit., H. perforatum L. and H. rochelii Griseb. & Schenk was conducted in the present study. Two types of herbal preparations obtained from the aerial parts of these species were analyzed: extracts ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…A number of drugs have been developed with the aim of modifying the activity of these enzymes that are vital in the pathophysiology of some of the frequent diseases. The obtained results have demonstrated moderate anticholinesterase and anti-MAO-B activity of the examined Hypericum extracts, with IC 50 values in the range 606.03-1304.04 µg/mL and 47.81-59.25 µg/mL, respectively (Table 2), which are in accordance with previous studies of these species [18], as well as H. perforatum extracts [2,12,25]. It can be easily noticed that the IC 50 values obtained for galantamine and selegiline under identical experimental conditions are significantly lower, which questions the acute effects of Hypericum extracts as inhibitors of AChE and MAO-B.…”
Section: Inhibition Of Biologically Important Enzymes Inhibition Of A...supporting
confidence: 89%
“…A number of drugs have been developed with the aim of modifying the activity of these enzymes that are vital in the pathophysiology of some of the frequent diseases. The obtained results have demonstrated moderate anticholinesterase and anti-MAO-B activity of the examined Hypericum extracts, with IC 50 values in the range 606.03-1304.04 µg/mL and 47.81-59.25 µg/mL, respectively (Table 2), which are in accordance with previous studies of these species [18], as well as H. perforatum extracts [2,12,25]. It can be easily noticed that the IC 50 values obtained for galantamine and selegiline under identical experimental conditions are significantly lower, which questions the acute effects of Hypericum extracts as inhibitors of AChE and MAO-B.…”
Section: Inhibition Of Biologically Important Enzymes Inhibition Of A...supporting
confidence: 89%
“…H. rochelii is a Balkan species that grows at altitudes of 500–1200 m on calcareous rocks [ 73 ]. Specimens have been found to contain phenolic acids, myricetin rhamnosides, other flavonoids in large amounts [ 74 ] and also the glucosylxanthones isomangiferin and mangiferin [ 75 ]. The authors focused on the polar phenolic compounds and did not comment on the presence of phloroglucinols.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published paper, which also used the microdilution method, showed that a 70% ethanol extract of H. rochelii from Romania had a significantly lower activity for Gram-positive bacteria, especially S. aureus , than our CO 2 and CH 2 Cl 2 extracts. Its MIC and MBC values were 250–1000 and 500–2000 mg/L, respectively [ 74 ]. It is possible that this was due to the polyprenylated phloroglucinols found in the extracts in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds from these groups have antibacterial and antioxidant potency plant extracts that have phenolic and flavonoid molecules, inhibiting bacterial growth as well as preventing cellular damage to the action of free radicles [ 33 , 59 , 63 , 64 ]. The extracts and essential oils from Hypericum species have demonstrated compounds with antibacterial and antioxidant properties [ 41 , 44 , 45 , 65 ]. However, there is no study that has been reported over the essential oils revived from the leaves or flowers of H. revolutum subsp.…”
Section: Discussionmentioning
confidence: 99%